A single pre-B cell can give rise to antigen-specific B cells that utilize distinct immunoglobulin gene rearrangements (The Rockefeller University Press, 1990)
A group of hybridomas that express antibodies with related specificities for the influenza virus hemagglutinin (HA), that represent B cells that were the clonal progeny of a single pre-B cell, and that utilized distinct L chain gene rearrangements have been characterized. The clonal relationship was established by the sharing of H chain gene rearrangements at both the productive and the nonproductive alleles. Among these hybridomas, one group had rearranged only one of its kappa alleles, having joined a V kappa 24 gene to the J kappa 2 gene segment. The other group utilized the same V kappa 24 gene segment in productive rearrangement to the J kappa 5 gene segment, and shared an aberrant rearrangements among members of the same B cell clone can normally occur, and can contribute to the generation and diversification of the immune repertoire that is available for the recognition of foreign antigens. Mechanisms by which the distinct rearrangements expressed by the hybridomas might have been generated are discussed.